The efficacy and safety of intrathecal pemetrexed for leptomeningeal metastasis from non-small cell lung cancer: a single-arm meta-analysis of Chinese patients - Zhao, Yushi; Gao, Xueqin; Han, Yong (Frontiers in Oncology, 2025)
ObjectivesThe purpose of this meta-analysis is to evaluate the safety and effectiveness of intrathecal pemetrexed (IP) in patients with non-small cell lung cancer with leptomeningeal metastasis (NSCLC-LM).MethodsA systematic search of PubMed, the Cochrane library, Embase, and ClinicalTrials.gov databases was executed until December 11, 2024. The quality of the selected studies was evaluated using the Risk Of Bias In Non-randomized Studies Of Interventions (ROBINS-I) tool. Data extracted encompassed disease control rate (DCR), objective response rate (ORR), median overall survival (mOS), and adverse events (AEs). A random-effects model was used in the meta-analysis, which was conducted using STATA 15.1 software. Egger’s and Begg’s tests were used to analyze publication bias, and when significant publication bias was detected, the Trim and Fill method was employed to adjust for the bias.ResultsThis meta-analysis included 8 studies involving a total of 306 patients, with a pooled ORR of 57.6% (95% CI: 39.5%-74.7%). Further subgroup analysis revealed that a pemetrexed dosage of 40–50 mg exhibited superior efficacy, with an ORR of 84.5% (95% CI: 70.0%-95.6%), compared to an ORR of 46.6% (95% CI: 29.2%-64.4%) for dosages of 10–30 mg. Additionally, patients with EGFR mutations exhibited an ORR of 56.2% (95% CI: 34.7%-76.6%), while those with other genetic subtypes had an ORR of 44.8% (95% CI: 25.1%-65.1%). The combined DCR was 85.4% (95% CI: 76.5%-92.7). In terms of survival, the pooled data from 6 studies yielded a mOS of 8.12 months (95% CI: 6.07-10.17). Common adverse events associated with pemetrexed included myelosuppression (32.6%), headache (24.8%), abnormal transaminase (11.8%), nausea (7.3%), vomiting (11.7%), radiculitis (8.4%) and leukoencephalopathy (6.4%). Potential publication bias was identified for DCR and grade≥III myelosuppression. Subgroup analyses performed by DCR showed that the bias was related to drug dosage, while the Trim and Fill method for grade ≥III myelosuppression did not reverse the bias. These findings suggest that publication bias had minimal impact and that the results were relatively stable.ConclusionsThis meta-analysis concludes that patients with NSCLC-LM benefit from intrathecal chemotherapy using pemetrexed.